Catering to otherness: Levinasian consumer ethics at restaurant day - Hietanen, Joel ca. 20./21. Jh. (Journal of business ethics, 2021)
There is a rich tradition of inquiry in consumer research into how collective consumption manifests in various forms and contexts. While this literature has shown how group cohesion prescribes ethical and moral positions, our study explores how ethicality can arise from consumers and their relations in a more emergent fashion. To do so, we present a Levinasian perspective on consumer ethics through a focus on Restaurant Day, a global food carnival that is organized by consumers themselves. Our ethnographic findings highlight a non-individualistic way of approaching ethical subjectivity that translates into acts of catering to the needs of other people and the subversion of extant legislation by foregrounding personal responsibility. These findings show that while consumer gatherings provide participants a license to temporarily subvert existing roles, they also allow the possibility of ethical autonomy when the mundane rules of city life are renegotiated. These sensibilities also create "ethical surplus", which is an affective excess of togetherness. In the Levinasian register, Restaurant Day thus acts as an inarticulable "remainder" - a trace of the possibility of being able to live otherwise alongside one another in city contexts.